MASSAGE COUNTER PRESSURE MEMPENGARUHI INTENSITAS NYERI HAID PADA REMAJA PUTRI - Henniwati Henniwati; Dewita Dewita (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
MASSAGE COUNTER PRESSURE AFFECT THE INTENSITY OF HAART PAIN IN ADOLESCENT PRINCESS Background: Menstrual pain is pain that almost all women feel during menstruation. In Indonesia, the incidence of dysmenorrhea is 64.25%. Treatments that can be given to reduce menstrual pain are suggested pharmacologically and non-pharmacologically. One of the non-pharmacological therapies that can be given is the counter pressure technique.Purpose: This study aims to determine the effect of counter pressure on the intensity of menstrual pain in adolescent girls.Method: the type of research used is a quasi-experimental design with a pretest-posttest one group design. The sampling technique used total sampling technique, the number of samples in this study were 36 young women at SMPN 9 Langsa City.Results: The results of the study were obtained at the pretest time the severe pain scale was 50%, and at the posttest after being given the treatment the pain scale decreased to a mild pain scale of 83.3%. The results of the Paired T-Test analysis showed that there was an effect of counterpressure on the intensity of menstrual pain in adolescent girls with a sig. 0,000.Conclusion: The couter pressure technique affects the intensity of menstrual pain in adolescent girls (P = 0,000).Suggestion: IUKS department in schools can provide counter pressure therapy to reduce menstrual pain that is felt by young women. Keywords: Menstrual Pain, Counter pressure,Adolescent ABSTRAK Latar Belakang : Nyeri haid merupakan nyeri yang hampir seluruh wanita rasakan pada saat haid. Di Indonesia angka kejadian dismenore sebesar 64,25%. Penanganan yang dapat diberikan untuk mengurangi nyeri haid yang disarakan secara farmakologi dan nonfarmakologi. terapi nonfarmakologi yang dapat diberikan salah satunya adalah tehnik counter pressure.Tujuan : penelitian ini bertujuan untukmengetahui pengaruh pemberian counter pressure terhadap intensitas nyeri haid pada remaja putri.Metode: jenis penelitian yang digunakan yaitu quasi eksperimendengan densain pretest- posttest one group desain. tehnikpengambilansampelmenggunakan Tehniktotal Sampling, jumlahsampel pada penelitian ini yaitu 36 remaja putri di SMPN 9 Kota Langsa.Hasil saat pretest skala nyeri berat sebesar 50%, dan pada saat posttest setelah diberikan perlakuan skala nyeri turun menjadi skala nyeri ringan 83,3%. Hasil analisis Paired T-Test menunjukan ada pengaruh pemberiaan counter pressure tehadap intensitas nyeri haid pada remaja putri denga nilai sig. 0,000.Kesimpulan : Tehnik counter pressure berpengaruh terhadap intensitas nyeri haid pada remaja putrid (P = 0,000).Saran : UKS di sekolah agar dapat memberikan terapi counter pressure untuk mengurangi nyeri haid yang dirasakan remaja putri. Kata Kunci : Nyeri Haid, Counter pressure,remaja